Estimating the effects of fiscal policy in OECD countries - Roberto Perotti (European Central Bank (ECB), 2002)
This paper studies the effects of fiscal policy on GDP, prices and interest rates in 5 OECD countries, using a structural Vector Autoregression approach. Its mains results can be summarized as follows; 1) The effects of fiscal policy on GDP and its components have become substantially weaker in the last 20 years; 2) The tax multipliers tend to be negative but small; 3) Once plausible values of the price elasticity of governments spending are imposed, the negative effects of government spending on prices that have been frequently estimated become positive, although usually small and not always significant; 4) Government spending shocks have significant effects on the real short interest rate, but uncertain signs; 5) Net tax shocks have very small effects on prices; 6) The US is an outlier in many dimensions; US responses to fiscal shocks are often not representative of the average OECD country included in this sample.
Keywords: E62; H30; 330